Antarctica Through The Archive: A Script - Polly Gould (Opticon1826, 2014)
This script explores the act of seeing clearly under special conditions, namely the extreme environment of Antarctica, and the contrasting environment of the archive. The archive is accessed through the watercolours of explorer Edward Wilson (1872-1912) and the photographs of Herbert Ponting (1870-1935). This text is presented as a script for, or transcript of, a lecture on the archival encounter with Antarctica, exposing those subjects that are not immediately visible but none-the-less intrinsic to it. As a transcript of what has already taken place, the text mimics the relation between historical event and archival evidence. As a script for future enactment, the text opens roles to other actors. This lecture is spoken among the new art works that have been made out of a process of imitation, emulation and distortion in response to watercolours and drawings in the Wilson archive. The two settings include the lecture’s contemporary situations, as well as the historical setting of Scott’s Antarctic expedition hut in 1911, in which lectures were given to educate and entertain the expedition crew. Archival references to the hut lectures include a photograph of Ponting lecturing on Japan with a magic lantern, and also Wilson’s pencil-written notes on the topic of sketching.
Keywords: watercolours; Herbert Ponting; Edward Wilson; Antarctica